Urine test for EGFR analysis in patients with non-small cell lung cancer - Franovic, Aleksandra; Raymond, Victoria M.; Erlander, Mark G.; Reckamp, Karen L. (Journal of Thoracic Disease, 2017)
Precision medicine approaches in oncology are reliant on the accurate genomic characterization of tumors. While tissue remains the mainstay specimen for molecular testing, tumor biopsies are riddled with challenges and limitations due to their invasive and site-specific nature. Tumor inaccessibility and intratumoral heterogeneity, in particular, represent significant obstacles to the identification of actionable genetic alterations and hence effective mono- and combination therapy strategies. Proof-of-concept studies indicate that circulating tumor DNA (ctDNA) released from multiple tumor regions and anatomical locations is more reflective of intra- and intertumoral heterogeneity. Non-invasive liquid biopsy approaches that allow for the analysis of ctDNA are thus being increasingly implemented in routine patient care for the detection and monitoring of cancer-associated mutations. Indeed, the use of plasma testing to screen for epidermal growth factor receptor (EGFR) T790M mutant positive non-small cell lung cancer (NSCLC) patients eligible for treatment with third-generation EGFR inhibitors was recently approved by the U.S. Food and Drug Administration and is incorporated into the most recent version of the National Comprehensive Cancer Center guidelines as an alternative to tissue biopsy. Urine represents another liquid biopsy specimen that is distinguished by its ease of collection, option for home collection, and lack of temporal and volumetric collection restrictions. Importantly, there is an accumulating body of evidence supporting the clinical validity of urinary EGFR mutant testing for the identification and stratification of patients likely to benefit from EGFR-directed therapies and as a means to assess patient response, the presence of residual disease, and emergence of resistant tumor cell populations.